Broad-scale recombination pattern in the primitive bird Rhea americana (Ratites, Palaeognathae) - del Priore, Lucía (2017)
Birds have genomic and chromosomal features that make them an attractive group to analyze the evolution of recombination rate and the distribution of crossing over. Yet, analyses are biased towards certain species, especially domestic poultry and passerines. Here we analyze for the first time the recombination rate and crossover distribution in the primitive ratite bird, Rhea americana (Rheiformes, Palaeognathae). Using a cytogenetic approach for in situ mapping of crossovers we found that the total genetic map is 3050 cM with a global recombination rate of 2.1 cM/Mb for female rheas. In the five largest macrobivalents there were 3 or more crossovers in most bivalents. Recombination rates for macrobivalents ranges between 1.8–2.1 cM/Mb and the physical length of their synaptonemal complexes is highly predictive of their genetic lengths. The crossover rate at the pseudoautosomal region is 2.1 cM/Mb, similar to those of autosomal pairs 5 and 6 and only slightly higher compared to other macroautosomes. It is suggested that the presence of multiple crossovers on the largest macrobivalents is a feature common to many avian groups, irrespective of their position throughout phylogeny. These data provide new insights to analyze the heterogeneous recombination landscape of birds.